2018
DOI: 10.1002/hed.25115
|View full text |Cite
|
Sign up to set email alerts
|

Double‐blind placebo‐controlled multicenter phase II trial to evaluate D‐methionine in preventing/reducing oral mucositis induced by radiation and chemotherapy for head and neck cancer

Abstract: Although not meeting the primary end point, results of multiple assessments suggest that D-met decreased mucositis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…D-met is contained in egg albumin [111]. The first researches on D-met properties focused on its efficacy in preventing cisplatin-induced ototoxicity in rat by its specific ability to counteract oxidative stress, without affecting the tumor response to an antineoplastic agent [112][113][114][115][116]. The D-met antioxidant activity is displayed also in other areas of the body: (i) in the liver, preventing the decrease of mitochondrial glutathione levels [117]; (ii) in the CNS, improving neurogenesis of hippocampal neurons [118]; (iii) in the kidney, through elevation of antioxidative activities [119]; and (iv) in the gastrointestinal system, protecting the mucosa and the gut microbiome from cisplatin-induced imbalance [120].…”
Section: D-methioninementioning
confidence: 99%
“…D-met is contained in egg albumin [111]. The first researches on D-met properties focused on its efficacy in preventing cisplatin-induced ototoxicity in rat by its specific ability to counteract oxidative stress, without affecting the tumor response to an antineoplastic agent [112][113][114][115][116]. The D-met antioxidant activity is displayed also in other areas of the body: (i) in the liver, preventing the decrease of mitochondrial glutathione levels [117]; (ii) in the CNS, improving neurogenesis of hippocampal neurons [118]; (iii) in the kidney, through elevation of antioxidative activities [119]; and (iv) in the gastrointestinal system, protecting the mucosa and the gut microbiome from cisplatin-induced imbalance [120].…”
Section: D-methioninementioning
confidence: 99%
“…For example, methionine-derivative S-adenosyl methionine (SAM) is a cofactor acting mainly as a methyl donor to cytosine in DNA during epigenetic modification [136]. A recent study found a reduced oral mucositis after an oral D-methionine treatment in patients with grade 3/4 HNSCCs [137]; an in vitro study showed that the administration of methionine could also downregulate the proliferative capacity in HNSCC cells; it was also reported that there was a positive correlation of high methionine serum levels with greater overall and relapse-free survival rates [121,138]. These findings suggest that methionine could be tumor-suppressive and that the methionine content might serve as a prognostic factor for HNSCC patients, although one must still mechanistically clarify the way in which methionine regulates epigenetic modification in HNSCC development.…”
Section: Development Of Anti-cancer Scheme By Targeting Distinct Mmentioning
confidence: 99%
“…R e p o r t s e x a m i n i n g a m i n o a c i d & a m i n o a c i d derivatives for OM are either preliminary or have shown no benefit (33)(34)(35)(36)(37)(38)(39)(40)(41). Similarly, no recommendation can be made on the use of alternative therapies.…”
Section: Discussionmentioning
confidence: 99%